The Epidemiological Pattern of COVID-19 Epidemic, During the Initial Phase in Thi-Qar Governorate, Iraq: A Case Series Study - Muslim Musa (The Medical Journal of Basrah University, 2020)
Background/ Aims: Understanding the epidemiological features and transmission dynamic during the initial phase of the COVID-19 epidemic provide valuable information for control and mitigation of the outbreak. Thus, this study focused on a cohort who represent early cases in Thi-Qar governorate for describing the early epidemiological features during the initial phase of the COVID-19 outbreak. Subject & Methods: This case series study was conducted in AL-Hussien Teaching Hospital, Thi-Qar governorate, from 27, February to 8, May 2020. Patient's data were obtained from official records of the Public Health Department of ThiQar Health Directory. A descriptive and analytical statistic were used by the aid of SPSS, also household secondary attack rate was estimated. Results: The median age was 37 years (IQR:31,20-51), females were 57.2% and males were 42.8%. According to age groups, as a higher infection rate (30.61% %) was found in the age group (14-26), while only (4%) found old age groups(66-78,79-91). Only six patients(12.25%) had comorbidities. Clinically, majority(79.6%) of cases were mild and (18.4%) moderate while only (4%) were severe. The age and comorbidities had an effect on the severity of symptoms. Family transmission(80.43%) was the predominant dynamic of disease transmission. Three index cases in this cohort fulfill the criteria of super-spreader as collectively transmitted the disease to 79.6% individuals, the household secondary attack rates were 22%, 24%, and 17% respectively. Conclusion: Family transmission was the predominant dynamic of transmission which was the result of the presence of a super-spreader event in the early infected patients in the governorate.